Vitrification of denuded buffalo (Bubalus bubalis) oocytes: Effects of ethylene glycol concentration and equilibration time - DHALI, A; MANIK, R S; DAS, S K; SINGLA, S K; PALTA, P (The Indian Journal of Animal Sciences, 2014)
Denuded buffalo oocytes were vitrified either in vitrification solution-I(VS-I) that conisted of 4.5 M ethylene glycol (EG), 3.4 M dimethyl sulphoxide, 5.56 mM glucose, 0.33 mM sodium pyruvate and 0.4% w/v BSA in DPBS, or in vitrification solution-II (VS)II) that contained 3.5 M EO, with other constituents at the same concentrations as in VS-I. Bcfore vitrilica.tioll, the oocytes were exposed to equilibration solution-I or II (prepared by 50%) dilution, vlv, of VS-I and VS-II, respectively, in DPBS for 1 or 3 min at 1'0001 temperature. The post vitrification recovery of morphologically normal oocytes were 92% and 77% in VS-I, and 85% and 84% in VS-II for the equilibration time 1 min and 3 min respectively. Following IVM, the nuclear maturation rate of these oocytes were 8% and 9% in VS-I, and 9% and 0% in VSÂ·II for the equilibration time 1 min and 3 min respectively